1981
DOI: 10.1007/bf02535020
|View full text |Cite
|
Sign up to set email alerts
|

α‐Tocopherol and serum lipoproteins

Abstract: Twenty-six patients with clinically confirmed mammary dysplasia and five age-matched controls were treated with alpha-tocopherol, 600 mg/day. Serum samples collected on the 21st day of the menstrual cycle were analyzed for cholesterol in lipoprotein fractions, isolated by a combination of precipitation and ultracentrifugation techniques. Eighty-five percent of patients showed objective and subjective remission from disease following therapy. In mammary dysplasia patients, the ratio of serum cholesterol/high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although more work has been published on the gonadotropins, LH and FSH, the evidence for any abnormality is equivocal. Urinary LH has been claimed to be either low [114] or normal [130] whilst serum LH has been found to be either high [68,185] or normal [90,113]. Most authors have reported normal urinary and serum FSH [90,114], although Mirabile et al [130] claimed that urinary FSH was low during the follicular and high in the luteal phase of the menstrual cycle.…”
Section: (D) Lh Fsh and Tshmentioning
confidence: 95%
See 1 more Smart Citation
“…Although more work has been published on the gonadotropins, LH and FSH, the evidence for any abnormality is equivocal. Urinary LH has been claimed to be either low [114] or normal [130] whilst serum LH has been found to be either high [68,185] or normal [90,113]. Most authors have reported normal urinary and serum FSH [90,114], although Mirabile et al [130] claimed that urinary FSH was low during the follicular and high in the luteal phase of the menstrual cycle.…”
Section: (D) Lh Fsh and Tshmentioning
confidence: 95%
“…No difference and no change after vitamin E treatment No significant difference in mean but some higher (>20ng/ml) levels in patients Bahu et al 1980 [10] Bischoff et al 1980 [14] Latteri et al 1980 [103] Tarquini et al i980 [188] Sundaram et al 1981 [185] Simkin 1982 [179] * BBD -benign breast disease.…”
Section: (C) Androgensmentioning
confidence: 98%
“…Vitamin E is transported by the plasma lipoproteins [3,50]. Several studies reported that vitamin E increased cholesterol levels in the HDL [3,50]. Other studies reported that vitamin E had little effect on plasma lipoproteins [4,51], and still other studies reported that vitamin E increased cholesterol levels in the VLDL and LDL [5,28].…”
Section: Resultsmentioning
confidence: 92%
“…However, vitamin E, unlike free cholesterol, is found in the lipid core of plasma lipoproteins [49]. Vitamin E is transported by the plasma lipoproteins [3,50]. Several studies reported that vitamin E increased cholesterol levels in the HDL [3,50].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the change in endogenous sterol excretion appeared to depend mainly on the magni tude of change in serum cholesterol, and not on the type of fat used. It has been suggested that the higher content of tocopherols and ubiquinones in germ oils may lower serum cholesterol in addition to the effect of the fatty acids [12,13,30,31], It is conceivable that these compounds could enhance the ac tion of polyunsaturated fatty acids in the body by protecting them against oxidation [32].…”
Section: Discussionmentioning
confidence: 99%